KONTEKS BUDAYA ETNIS TIONGHOA DALAM MANAJEMEN SUMBER DAYA MANUSIA - Setyawan, Surya (Benefit, 2005)
Cultural context of every nation and ethnic have specific characteristic. Variety of this culturalcontext can make conflict with organizations, which also have specific characteristic. Tionghoa ethnicwhich have specific cultural context from their ancestor inheritance is example of cultural contextmanagement in organization, especially human resource management.